Implementasi Pembelajaran Pendidikan Agama Islam dalam Pembentukan Akhlak Siswa di SMP Sains Quran Pekanbaru - Nininig Suniarti (Jurnal Pendidikan Islam Indonesia, 2026)
This research is motivated by the importance of implementing Islamic Religious Education (ISE) in shaping students' morals amidst the changing times and the influence of globalization, which increasingly influence student behavior. Islamic Religious Education plays a crucial role in instilling religious values ​​and shaping students' character, leading to noble morals. This study aims to examine the implementation of Islamic Religious Education (ISE) in shaping students' morals, as well as the supporting and inhibiting factors at Pekanbaru's Quranic Science Junior High School. This study employed a qualitative approach with descriptive research. Data collection techniques included observation, interviews, and documentation. The research informants included the principal, ISE teachers, homeroom teachers, and students. Data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that the implementation of ISE through classroom learning, religious activities, and teacher role models. These activities can improve students' discipline, responsibility, and religious attitudes. Supporting factors include school support, teacher competence, and Islamic school culture, while inhibiting factors include external environmental influences, social media, and lack of family supervision.